Evaluation of the dose metric for acute lung inflammogenicity of fast-dissolving metal oxide nanoparticles. Issue 10 (25th November 2016) - Jeong, Jiyoung; Lee, Seonghan; Kim, Sung-Hyun; Han, Youngju; Lee, Dong-Keon; Yang, Jun-Young; Jeong, Jayoung; Roh, Changhyun; Huh, Yun Suk; Cho, Wan-Seob
Abstract: Although surface area metric was suggested as an appropriate dose metric for acute lung inflammation of NPs, it might not be effective for fast-dissolving NPs because they lose their reactive surface when dissolved in the phagolysosomes. Herein, we evaluated the dose metric for fast-dissolving NPs using a rat intratracheal instillation model. A panel of fast-dissolving NPs (CoO, CuO and ZnO) and their constituent metal ions (CoCl2, CuCl2 and ZnCl2 ) were compiled and each compound was intratracheally instilled into the lungs of female Wistar rats at the same molar concentrations in the NP doses (40, 100 and 400 μg/rat). The toxicity endpoints including cytological and biochemical data in bronchoalveolar lavage fluid were evaluated at 24 h after instillation. To evaluate the dose metric, each toxicity endpoint was plotted against the instilled dose (mass or surface area) or the equivalent dose (mass or surface area) that was weighted by the ratio of specific dose-generated responses between metal chlorides. Dose-response curves of fast-dissolving NPs about percentage of granulocytes, lactate dehydrogenase levels and total protein levels showed similar pattern but slightly less potential than those of their respective metal chlorides. When each toxicity endpoint was plotted against the equivalent mass dose, three types of NPs showed more overlapping dose-response curves than other dose metrics. In conclusion, this study implies that the equivalent mass dose is an appropriate dose metric for fast-dissolving NPs and the main factor determining the slope of the dose-response curve is the intrinsic toxicity of the their constituent ions.